Phytochemical screening and evaluation of the central nervous system activity of the ethanolic extract of Eugenia clarensis Britton & P.Wilson - Nghia TM. Nguyen; Liliana Vicet-Muro; Dany Siverio-Mota; Maria E. Jorge-Rodriguez; Dulce M. González-Mosquera; Idelfonso Castañeda-Noa (GarVal Editorial Ltda., 2016)
Context: Eugenia clarensis Britton & P. Wilson is an endangered plant endemic of central region of Cuba. Aims: To perform phytochemical profile of ethanolic leaf extract of E. clarensis and evaluate its central nervous system (CNS) activity. Methods: The dried powder of leaves of E. clarensis was exhaustively extracted with ethanol by maceration. This extract underwent preliminary phytochemical analysis and these results were corroborated by the thin layer chromatographic technique. CNS effects were investigated in NMRI mice at doses 200, 400 and 800 mg/kg using Irwin test, curiosity tests and traction. Results: Phytochemical screening suggested the presence of phenols, tannins, triterpenoids, sterols, flavonoids, coumarins, quinones, resins and reducing sugar. The oral administration of this extract, in Irwin test, produced slight reduction in spontaneous motor activity and muscle tone in mice at doses of 400 and 800 mg/kg, moreover, it exhibited diuretic activity. In addiction this extract at dose 800 mg/kg decreased number of times which mice introduced its head into holes in comparison with the negative control. In the traction test, the mice treated with the extract showed a non-significant failure in traction at all doses tested. Conclusions: These findings indicate that the extract in higher doses has exerts a weak sedative and non-effect about the motor coordination. The results obtained in the preliminary phytochemical testing thus suggest that the ethanolic leaf extract of E. clarensis contains some metabolites, which may be responsible of sedative action.